Restraint Use and Delirium in Critical Care in England and Wales: A Current Law Review - Attila Lakatos RGN, MA (SAGE Publishing, 2020)
Introduction This is a law review of restraint use in critical care settings within the United Kingdom with a specific context to England and Wales following the introduction of new statues and case law developments. The principles discussed could be similarly applied internationally, as the aim of health care is the preservation of life. Care delivery often proves difficult without the use of restraint considering the adversities delirium may present with as a common occurrence. Staff have to be aware of their role, duty, and limitations in legal terms and respond to challenging behavior appropriately and proportionately within the law. Methods As a law review, it follows arguments and principles around a topic by analyzing case law and statutory instruments specifically applicable to restraint use within critical care. Conclusion Restraint use in critical care settings in England and Wales is justifiable prior to formal authorization regardless the patient has or lacks capacity at the time as long as the restraint use is to maintain life-sustaining treatment or where an action could result in potential deterioration in the condition of the patient. However, there is a need to distinguish between on-going and life-sustaining care provisions. Restraint use in any case has to be in order to protect the patient from harm, enacted in the best interest of the patient, and has to be proportionate with the perceived likelihood of severity of likely harm occurring. Unless the delirium lasts or likely to last for over 28 days, no formal application is required should the need arise. Staff are empowered by statutory and case law measures to act with the use of appropriate restraint to protect their patients and those in close vicinity from harm. Regardless of national jurisdictions, the aim of critical care is to preserve life; hence, the findings within could be applicable internationally.